Signals for Entrepreneurial Family Lending: Psychological Capital as an Intent Signal - Zhou, Xue; Zhang, Ling; Su, Xiaoyun; Shirshitskaia, Ekaterina (Frontiers in Psychology, 2022)
Family financing has become a powerful channel for entrepreneurs to obtain entrepreneurial funding. How do family members use intent and quality signals to select new ventures to provide lending support? Building on the signaling theory, this study provides the first quantitative evidence using a sample of 166 samples of family lenders in China. Our findings reveal that psychological capital can support entrepreneurs to obtain family lending. As an intent signal, psychological capital becomes more influential when quality signals, corporate competitive advantage, and firm performance perform more positively. This study emphasizes that family financing support is not only out of love or altruism and extends the literature concerning the influence of positive psychological capital in financial investment decisions.